Genre trends in Anna Akhmatova’s poetry: to the question of the traditions - Чаунина, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article considers the key genre trends in Akhmatova’s poetry. The term «dominant installation of the author» (Kighney’s term) is used as the main genre-make criterion. The introspective, formally canonical, functional installations are defined and analysed. The conclusion of the article is that the author's installations, inspired by the needs of time and tradition, and may be embodied in an individual poetic work in the syncretic, differently interpreted genre structures.